EKSTRAKSI KEMIRI DENGAN METODE SOXHLET DAN KARAKTERISASI MINYAK KEMIRI - Ariestya Arlene (Jurnal Teknik Kimia USU, 2013)
Candlenut is originally from Hawaii. This plant is then spread all over the countries, including Indonesia, and firstly grow in Maluku. Candlenut becomes domestic and foreign commodities in Indonesia. This plant is known well because the seed is often used as the cooking ingredient. The seed of candlenut contains a large amount of oil, which is 50-60% from the mass of the seed. Candlenut oil is used as hair fertilizer, paint materials, and varnish material. With further research, candlenut oil is expected to be applied in wider scope. The aim of this research is to extract the candlenut oil from its seed maximally with Soxhlet extraction method. The benefit of this research is to give inputs and information about the suitable solvent that influence the oil extraction from candlenut seed, which can increase the use of candlenut as natural resource and support the other industries. The method of this research consists of early treatment of candlenut seed, Soxhlet extraction with acetone, ethanol, and n-hexane as solvent, then continued with the analysis of the oil. The conclusion of this research are the solvent which produce the highest yield in oil extraction of candlenut seed is n-hexane, with the yield value is 74,57% from the mass of the seed. However, the best quality of the candlenut oil is obtained from extraction with ethanol as the solvent, with the acid value is 8,27 gram KOH/gram oil. Keywords: soxhlet, candlenut, acetone, ethanol, n-hexane